Analisis Citraan Buku Tunas Bangsa Penuh Pengorbanan sebagai Bahan Ajar Menulis Puisi bagi Siswa Kelas IV Sekolah Dasar - Musriyati, Lilik; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Children's literature plays an important role in the stage of child development, through children's literature adults can communicate with children so that literature can be used to improve language skills and abilities. One aspect of language skills is writing skills. In fact, there is still a lack of writing skills, especially writing poetry, one of the reasons is that students think writing is an exciting and less interesting activity. In the 2013 curriculum writing poetry is contained in learning Indonesian for grade IV elementary school. In writing poetry, it is necessary to have an image or imagination as a picture that beautifies the work. The purpose of this study was to find out the kinds of images contained in the book Tunas Bangsa Penuh Pengorbanan, based on the analysis, it was used as teaching material for writing poetry for fourth-grade elementary school students, teaching materials were made that were interesting, innovative and easy for students to understand to increase creativity in ideas student. Data collection techniques using document analysis and analysis techniques using data reduction, data display, and data verification. Based on the research, obtained as many as 6 kinds of imagery in the book Tunas Bangsa Penuh Pengorbanan, including 45 visual images, 31 auditory images, 4 tactile images, 7 movement images, 3 smell images, and 14 intellectual images. From these findings, the book of Tunas Bangsa Penuh Pengorbanan contains quite a lot of imagery that can be used as teaching materials for elementary school students writing. This book with many varied images is very suitable to be used as a material for stimulating students' imagination when learning to write.